Overcoming Traditionalism and Weak Internalization of Islamic Values in School - Sarwoedi; Syamsir (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
This study aims to examine the problem of traditionalism in teaching and the weak internalization of Islamic values in public schools, specifically at SMAN 10 Rejang Lebong. Using a qualitative approach involving observation, interviews, and questionnaires, the research found that Islamic Religious Education (IRE) classes remain dominated by passive lecture methods, limiting students’ active engagement. Islamic values are not yet systematically embedded within the school culture, and support from family and social environments is also minimal. The study integrates theories from Piaget, Vygotsky, Bronfenbrenner, and Mezirow’s Transformative Learning to interpret the findings. These results affirm previous research while introducing a new transformative learning model based on school culture integration. This research contributes a fresh perspective to Islamic education management in public schools and highlights limitations related to the scope and sample of the study.